Islamic psychotherapy formulation: considering the Shifaul Qalbi Perak Malaysia psychotherapy model - Khairunnas Rajab; Che' Zarrina (IAIN Salatiga, 2017)
Psychological issues faced by human beings in this modern era must be taken into account by psychologists, psychotherapists, psychiatrists, physicians, and observers of psychological problems. The existence of psychotherapists and institutions that provide treatment to recover people suffering from psychological problem is very important. Data of the Ministry of Health of the Republic of Indonesia of 2011 show that the number of adult population in Indonesia reached 150 million and approximately 11.6%, or 17.4 million of them suffered from mental disorder, such as anxiety and depression. This fact enables researchers to study and examine implementation of a psychotherapy model at Shifaul Qalbi (House of Shiqal) in recovering mental disorders due to the effect of drug addiction. Shifaul Qalbi applies the IMEJ (Iman, Mental,Emosi and Jasmani) (Faith, Mental, Emotion and Physics) psychotherapy model. Through this model, the recovery process can run optimally. IMEJ is synergetic formulation. These four components are integrated implemented. Faithful patients must have a healthy mental condition, controlled emotion, and strong physics. IMEJ is very essential and in line with the mental stages known as Jujur, Amanah, Tanggungjawab, dan Ikhlas (JATI) (honest, trustworthy, responsible and sincere). House of Shiqal prioritizes awareness and sincerity for itsoperation. The awareness and sincerity of the therapist makes the house succeed in recovering more than 92% of 1,000 patients that have been recovered from drug abuse since 2008.Persoalan psikologis yang menghadang manusia modern di abad ini, perlu diambil perhatian serius pihak-pihak terkait. Eksistensi psikoterapis dan lembaga-lembaga perawatan dan pemulihan adalah keharusan. Menurut catatan Kementerian Kesehatan RI tahun 2011, dari populasi orang dewasa di Indonesia yang mencapai 150 juta jiwa, sekitar 11,6 % atau 17,4 juta mengalami gangguan mental, seperti kecemasan dan depresi. Realitas ini, membuka ruang penelitian dan pengkajian, untuk menilik implementasi model Psikoterapi Shifaul Qalbi dalam membaik-pulih kesehatan mental, efek penagihan narkoba. Psikoterapi Shifaul Qalbi menerapkan model Psikoterapi Iman, Mental, Emosi, dan Jasmani (IMEJ). Melalui pendekatan IMEJ, proses pemulihan dapatberjalan optimal. Iman, Mental, Emosi, dan Jasmani adalah formulasi yang bersinergi. Empat komponen tersebut, diimplementasikan terintegrasi. Pasien yang beriman, mestilah memiliki mental yang sehat, emosional yang terkendali, dan jasmani yang kuat. Iman, Mental, Emosi, dan Jasmani (IMEJ) esensial dengan tahapan-tahapan mental yang disebut sebagai Jujur, Amanah, Tanggungjawab, dan Ikhlas (JATI). Penelitian ini dilakukan sebagai penelitian deskriptif kualitatif untuk mengkaji aspek psikologis pasien narkoba. Penelitian ini tidak dimulai dari deduksi teori, tetapi diawali dari fakta empiris di Syifa’ul Qalbi. Peneliti secara langsung ke Syifa’ul Qalbi dalam menemukan data yang terjadi secara alami, untuk kemudian mencatat, menganalisis, menafsirkan dan menarik kesimpulan-kesimpulan dari proses tersebut. Psikoterapi Shifaul Qalbiadalah Rumah Shiqal yang mengutamakan kesadaran dan keikhlasan bagi kelangsungan psikoterapi. Dengan kesadaran dan keikhlasan Rumah Shiqal telah merawat pasien narkoba bersignifikan bebas dari penagihan narkoba.